Genetic control of body weight by the human brain proteome - Eloi Gagnon; Arnaud Girard; Émilie Gobeil; Jérôme Bourgault; Christian Couture; Patricia L. Mitchell; Claude Bouchard; Angelo Tremblay; Patrick Mathieu; Andréanne Michaud; Louis Pérusse; Benoit J. Arsenault (iScience, 2023)
Summary: Genome-wide association studies (GWAS) have identified hundreds of genetic variants associated with body weight but the biological relevance of most remains unexplored. Given the critical role of the brain in body weight regulation, we set out to determine whether genetic variants linked with body mass index (BMI) could be mapped to brain proteins. Using genetic colocalization, we mapped 25 loci from the largest BMI GWAS (n = 806,834) to brain protein concentrations obtained from publicly available datasets. We also performed a proteome-wide Mendelian randomization on 696 brain proteins followed by genetic colocalization and identified 35 additional brain proteins. Only a minority of these proteins (<30%) had a colocalization signal with cortex gene expression levels, highlighting the value of moving beyond gene expression levels and examining brain protein levels. In conclusion, we identified 60 unique proteins expressed in the brain that may be critical regulators of body weight in humans.